Rancangan Pembuatan API Website Data Tanaman Obat Dan Langka Kabupaten Kediri - Shandy Arshad Busro Cahyono Busro; Sucipto; Rina Firliana; M Najibuloh Muzzaki; Anita Sari Wardani; M Iqbal Khalid; Adhi Wicak Milbar Gamas; Heru Setiawan (Bulletin of Information Technology (BIT), 2022)
The design of a website for information on medicinal and rare plants in Kediri Regency aims to provide convenience in obtaining information easily and quickly. The design of this website uses the Software Development Life Cycle (SLDC) Waterfall method with the stages of identification, analysis, design, implementation and testing. The web-based Application Programming Interface (API) uses Node.js as a runtime environment for the JavaScript programming language using the Express.js framework. The Application Programming Interface (API) is used as a liaison between the client and server, testing the endpoint Application Programming Interface (API) using Postman tools by displaying the results of the test in the form of data in JSON (JavaScript Object Notation) format which is used to store and transfer data